Qualitative Study of the Role and Practice of Pharmaceutical Services Focusing on Stunting by Community Pharmacists in Indonesia - Firdawati Amir Parumpu; Pratiwi Wikaningtyas; Satibi Satibi; Septi Muharni; Ananda Putri Purwanto; Kusnandar Anggadiredja (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: The peak of Indonesia's demographic bonus period is estimated to be in 2035, requiring government efforts in an integrated stunting prevention program to minimize risks. Cross-sector and cross-profession collaboration in the health field is needed to support optimal stunting services through the role and practice of pharmacists in community pharmacy facilities. This study aims to explore two topics: the role of community pharmacists and the practice of pharmaceutical service in stunting prevention programs in Indonesia. Methods: A pragmatic qualitative-descriptive study, using structured interview techniques with a Standardized Open-Ended Interview (SOEI). Nine community pharmacists were recruited using purposive sampling through interview consent. The data obtained from the interviews consisted of video and audio recordings that were transcribed, and then thematically analyzed. Results: The findings of this study are mapped into two main domains. The roles are identified as 1) The role of pharmacists in stunting prevention education through educational services, 2) in cross-sector collaboration among healthcare workers to prevent stunting in the community, and 3) in pharmaceutical services specifically for stunting prevention, which reflects practices in community pharmacy facilities in providing 4) basic education and counseling services related to stunting, 5) pharmaceutical product services for stunting needs, 6) promotive and preventive services in the stunting program, and 7) curative and referral services in the stunting program. Conclusion: These findings indicate a high level of awareness and professional competence among community pharmacists, and practices in the field show involvement and collaboration that can be integrated into Indonesia's health policy system in the future.